Theoretical calculation of energy conversion efficiency of an InGaN/InN quantum well intermediate band bifacial solar cell - Chavarry Mori, Herman; Sobrados Usquiano, Johel; Obispo Vasquez, Angel Eduardo; Villavicencio Gastelu, Joel; Jirón Vicente, Andres Guiseppe (LACCEI, 2024)
In this work, a simple mathematical model is introduced for the theoretical evaluation of energy conversion efficiency in InGaN/GaN/InGaN intermediate-band bifacial solar cells, highlighting the impact of well size and effective albedo. The variation in the efficiency with the width of the quantum well and under different albedo conditions, including green grass and pavement, was investigated. The results show that the solar cell efficiency can reach 65% for green grass albedo and 51% for pavement albedo at an optimal well width, surpassing the efficiency under standard AM 1.5G conditions without albedo reflection. This study underscores the effect of effective albedo on the conversion efficiency of bifacial solar cells and provides insights for the design and optimization of these systems in urban environments.